Evaluation of Farmers Management Practices of Arabica Coffee Plantation Across Altitude for Climate Change Adaptation Strategies in Aceh, Indonesia - Ashabul Anhar; Heru P. Widayat; Ali Muhammad Muslih; Subhan Subhan; Romano Romano; Akhmad Baihaqi; Teuku Saiful Bahri; Zulkarnain Zulkarnain; Bagio Bagio; Yusmaizal Yusmaizal; Yusya Abubakar (Graduate Program of Syiah Kuala University, 2020)
The productivity of Arabica coffee in low-altitude areas in Aceh have been declined, caused by an increase in temperatures, and by pests and diseases attack. This study aims to develop adaptation strategies to climate change in Aceh trough understanding how coffee productivity correlates with the management practices across the altitude. To find out a correlation between farming practices variables and coffee productivity, Spearman's rank test was used. To assess whether farming practice explanatory variables affected by the altitudes, a non-parametric with the Kruskal-Wallis Test, with Tukey’s post-hoc test (P0.05) with Chi-square distance were used. The results showed that coffee productivity was positively and significantly correlated to pruning, weeding, application of fertilizer, and application of pest and disease control, but was not to coffee plant density, sustainability certification, land conservation, and age of the coffee plant. Adaptation strategies for farmers in higher altitudes are to maintain the coffee plant density as well as shade density at an optimum level, followed by increasing management practices such as pruning, weeding, application of fertilizer, and pest and diseases control; in lower altitudes, those are to increase shade density both with Leucaena and multipurpose plants such as avocado and citrus, as well as increasing management practices such as land conservation, pruning, weeding, application of fertilizer and pest and diseases control. In middle altitudes, those are to maintain and improve management practices applied